MENINGKATKAN PERTUMBUHAN NASABAH BANK SYARIAH : MENDUKUNG PEMBIAYAAN PROMOSI, PENDIDIKAN DAN PELATIHAN - RONI ANDESPA (Maqdis: Jurnal Kajian Ekonomi Islam, 2016)
The research theme is the concept of business according to Islamic economics. The object of research is the existing sharia banks in Indonesia. The purpose of research are: 1) To see the effect of promotion costs on customer growth of sharia banks, 2) To see the effect of the cost of education and training on customer growth of sharia banks. The research variables are: 1) The independent variable (cost of promotion, education and training), 2) The dependent variable (customer growth). The study design was quantitative. This type of research is causality. The analytical tool used is multiple linear regressions. The data is used is secondary Data Obtained from Bank Indonesia. The data is in use are: 1) Cost of promotion in sharia banks, 2) The cost of education and training in sharia banks, and 3) The number of accounts in sharia banks. The results of the research are: 1) The cost of promotion has a significant influence on the growth of the customer, 2) The cost of education and training has a significant influence on the growth of the customer.